Genetic Structure and Diversity of the Endemic Carolina Madtom and Conservation Implications. (23rd April 2021) - Cope, W. Robert; Kwak, Thomas J.; Black, Tyler R.; Pacifici, Krishna; Harris, Sheila C.; Miller, Caitlin M.; Raley, Morgan E.; Hallerman, Eric M.
Abstract: Identification and conservation of genetic diversity within and among freshwater fish populations are important to better manage and conserve imperiled species. The Carolina Madtom Noturus furiosus is a small, nongame catfish that is endemic to the Tar and Neuse River basins of North Carolina. Genetic structure has not been studied in the species, and given recent population declines in both basins, identification of remaining genetic diversity within the species is vital for informing conservation efforts. To assess the status and trends of Carolina Madtom genetic structure, we analyzed genetic markers from 173 individuals to (1) define population genetic structure, (2) assess intra‐ and interbasin genetic differentiation in the Tar and Neuse River basins, and (3) present management implications to guide conservation efforts. Using 10 microsatellite primers developed for the related Yellowfin Madtom N. flavipinnis, we observed low genetic diversity in Carolina Madtoms. Genotype frequencies within samples were not in Hardy–Weinberg equilibrium, with a deficit of heterozygotes that could be due to family structure, inbreeding, or segregation of null alleles. Mean (±SD) M ‐ratios for the Tar River (0.414 ± 0.117) and Neuse River (0.117 ± 0.102) basin collections indicated that both populations have experienced recent demographic bottlenecks, with that in the Neuse River basin population being more severe. Effective population size estimates for the respective populations were small, on the order of tens of individuals, driving low genetic diversity within populations. However, the multilocus population differentiation metrics G ST ′ (mean ± SE = 0.135 ± 0.031) and D EST (0.125 ± 0.029) were significantly different from zero ( P < 0.001), indicating significant genetic differentiation between the Tar and Neuse River basin populations. Our findings will inform managers on the status of genetic variation in the Carolina Madtom and will guide conservation toward protective listing and management decisions to maintain the viability of this important endemic species.